Virucidal Influence of Ionic Liquids on Phages P100 and MS2 - Fister, Susanne; Mester, Patrick; Sommer, Julia; Witte, Anna K.; Kalb, Roland; Wagner, Martin; Rossmanith, Peter (Frontiers in Microbiology, 2017)
An increasing number of publications describe the potential of ionic liquids (ILs) as novel antimicrobials, antibacterial coatings and even as active pharmaceutical ingredients. Nevertheless, a major research area, notably their impact on viruses, has so far been neglected. Consequently the aim of this study was to examine the effects of ILs on the infectivity of viruses. A systematic analysis to investigate the effects of defined structural elements of ILs on virus activity was performed using 55 ILs. All structure activity relationships (SARs) were tested on the human norovirus surrogate phage MS2 and phage P100 representing non-enveloped DNA viruses. Results demonstrate that IL SAR conclusions, established for prokaryotes and eukaryotes, are not readily applicable to the examined phages. A virus-type-dependent IL influence was also apparent. Overall, four ILs, covering different structural elements, were found to reduce phage P100 infectivity by ≥ 4 log10 units, indicating a virucidal effect, whereas the highest reduction for phage MS2 was about 3 log10 units. Results indicate that future applications of ILs as virucidal agents will require development of novel SARs and the obtained results serve as a good starting point for future studies.